1995
DOI: 10.1111/j.1532-5415.1995.tb06620.x
|View full text |Cite
|
Sign up to set email alerts
|

Weight Change and Physical Function in Older Women: Findings from the Nun Study

Abstract: Monitoring of weight may be an easy and inexpensive method of identifying older individuals at increased risk of disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 16 publications
1
45
2
Order By: Relevance
“…This association has also been seen in a number of epidemiologic and clinical studies that adjusted for comorbidity, 5,7,13 disability, 5,13 smoking, 5,7 alcohol use 5 or level of physical activity 13 and that excluded deaths within the first few years of weight loss to exclude undiagnosed illness. 7 In frail elderly populations, even small weight loss (e.g., 1 kg, 5 or 3% of body weight 18 ) may be significant. Voluntary weight loss among elderly patients is also associated with increased risk of death 17 and of hip fracture, 19 which highlights the importance of maintaining weight with age.…”
Section: When Is Weight Loss Clinically Important?mentioning
confidence: 99%
“…This association has also been seen in a number of epidemiologic and clinical studies that adjusted for comorbidity, 5,7,13 disability, 5,13 smoking, 5,7 alcohol use 5 or level of physical activity 13 and that excluded deaths within the first few years of weight loss to exclude undiagnosed illness. 7 In frail elderly populations, even small weight loss (e.g., 1 kg, 5 or 3% of body weight 18 ) may be significant. Voluntary weight loss among elderly patients is also associated with increased risk of death 17 and of hip fracture, 19 which highlights the importance of maintaining weight with age.…”
Section: When Is Weight Loss Clinically Important?mentioning
confidence: 99%
“…9 Furthermore, Cossonelo et al 10 reported that multiple health problems were positively associated with poor cognitive performance.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Weight loss between two time points has been associated with increased risk of disability among women but not men. 24,26 The objectives of this study therefore were (i) to investigate the effects of current obesity, steady weight change and weight¯uctuation on poor physical functioning and (ii) to determine whether these associations were independent of coronary heart disease. All the participants in the Whitehall II study were employed in the British Civil Service at recruitment and therefore represent a comparatively young, high functioning population.…”
Section: Introductionmentioning
confidence: 99%